Erythemal UV Radiation on Days with Low UV Index Values—an Analysis of Data from the German Solar UV Monitoring Network over a Ten‐year Period. (25th March 2019) - Lehmann, Maria; Sandmann, Henner; Pfahlberg, Annette B.; Uter, Wolfgang; Gefeller, Olaf
Abstract: According to the World Health Organization and partner organizations, no protection against ultraviolet (UV) radiation is required on days with "low" values (i.e., values <3) of the Global Solar Ultraviolet Index (UVI). Erythemal irradiance ( E er ) data of such days were analyzed to evaluate this claim. Measurements from 9 stations of the German solar UV monitoring network from 2007 to 2016 yielded 14, 431 daily E er time series of low UVI days. Erythemal doses for certain fixed time intervals—acquired from measurements on horizontal planes—were compared with the average minimal erythemal dose (MED) of skin phototype II. Doses from days with rounded UVI values of 0 were insufficient to induce erythema and even on days with rounded UVI values of 1 doses exceeding 1 MED of skin type II could only be acquired under very specific circumstances of prolonged exposure. Conversely, sun exposure on days with rounded UVI values of 2 can indeed provide doses sufficient to induce erythema in skin type II after two hours around noon. In conclusion, our analyses do not support the claim of harmlessness currently associated with the entire low UVI exposure category in public guidance on interpretation of the UVI. Abstract : Current WHO guidance for sun exposure on days with Global Solar UV Index (UVI) values of less than 3 does not see any need for sun protection on these days. Contrary to this, our analysis of erythemal irradiance data of such days from the German solar UV monitoring network shows that doses resulting from exposure of only two hours around solar noon can be sufficient to induce erythema in fair‐skinned people on days with UVI values of 2, thereby questioning the WHO claim of harmlessness for this part of the low exposure category of the UVI.